Synthesis of Cassava Waste Pulp-Acrylamide Super Absorbent: Effect of Initiator and Cross-Linker Concentration - Zainal Alim Mas’ud; Mohammad Khotib; Nurmutia Sari; Anwar Nur (Indonesian Journal of Chemistry, 2013)
Cassava waste pulp (CWP) contains high carbohydrates that can be modified into super absorbent polymer (SAP) through grafting and cross-linking copolymerization. Acrylamide (AM) was grafted onto CWP with ammonium persulfate (APS) as the initiator and N,N'-methylene-bis-acrylamide (MBA) as the cross-linker under atmospheric nitrogen. The effect of APS and MBA concentrations on water absorption capacity of saponified SAP was studied, while the evaluation of grafting ratio (GR) and grafting efficiency (GRE) was conducted on unsaponified SAP. The grafting success was indicated by the occurrence of IR peaks at wave numbers of 573, 765, 858, and 1667 cm-1. In the saponified SAP, the very intense characteristic band at 1562 cm-1 is due to C=O asymmetric stretching in the carboxylate anion. Saponification increases significantly water absorption capacity compared to that of unsaponified SAP (from 39.79 g/g to 578.23 g/g). The highest water absorption capacity is reached at 0.74% APS and 0.09% MBA. The percentage of GRE and GR tends to increase with increasing APS concentration until reaching the highest value and then decreases. Effect of MBA concentration on water absorption capacity, GR, and on GRE is similar to the effect of initiator concentration on GR and GRE.